ADVANCEMENTS IN DENTAL RADIOGRAPHY AND RADIATION SAFETY: A KAP REVIEW OF DIGITAL IMAGING AND CBCT AMONG DENTAL PROFESSIONALS (Asian Journal of Medical Research and Health Sciences, 2026)
Advancements in dental radiography particularly digital imaging and Cone Beam Computed Tomography (CBCT) have enhanced diagnostic capabilities across dental specialties. Yet, these modalities also raise significant concerns about ionizing radiation exposure. This review evaluates the knowledge, attitudes, and practices (KAP) of dental professionals regarding advanced imaging and radiation safety. Recent cross-sectional studies reveal that while awareness of digital radiography (e.g., RVG) is high, familiarity with CBCT remains limited (around 58.9%). Further, systematic reviews highlight wide variability in knowledge (6–73%) and positive attitudes (16.8–84.8%) towards radiation protection, with actual safety practices lagging (19.8–64%). Region-specific surveys—for instance in Western Maharashtra show that although practitioners often perform clinical evaluations before imaging (100%) and use protective shields (98%), there are notable gaps in informed consent (only 87%), explaining risks (74%), and use of film-holding devices (28%). Addressing these gaps requires a structured KAP framework tailored to local institutions like Santosh Dental College, Ghaziabad. We propose a validated multi-section questionnaire (knowledge of CBCT/digital imaging and protective protocols; attitude towards radiation risks; practice of safety measures), followed by educational interventions (seminars, hands-on training, guideline dissemination) and pre/post-intervention assessments. Such an approach aims to align technological proficiency with ethical, safe practices in dental radiography, ensuring radiation protection is deeply embedded in clinical routines.